What constitutes recovery in schizophrenia? Client and caregiver perspectives from South India. (March 2020) - Gopal, Subhashini; Mohan, Greeshma; John, Sujit; Raghavan, Vijaya
Background: Understanding the concept of recovery in severe mental illnesses such as schizophrenia from the social and cultural aspects is important as it will help in developing models of recovery and appropriate interventions. Client and caregiver perspectives on recovery play a significant role in shaping these models and interventions. Hence, the aim of this study was to understand how clients with schizophrenia and their caregivers perceive recovery and to examine the differences between male and female clients with schizophrenia. Materials and methods: A total of 100 clients with schizophrenia and 80 caregivers of clients with schizophrenia were included in the study after written informed consent. A semi-structured proforma was used to collect the sociodemographic profile and illness variables. A questionnaire was developed to assess the indicators of recovery from mental illness and was administered to study participants. Descriptive statistics including frequency and percentages were used along with the chi-square test for analysis. Results: The most common indicators of recovery for the clients with schizophrenia were absence of symptoms (88%), no relapse (70%) and going back to work (70%), while for the caregivers were absence of symptoms (100%), becoming independent (92.5%) and no relapse (91%). Indicators of recovery were similar between male and female clients with schizophrenia except for the need to stop medication as an indicator of recovery observed significantly more in females ( p = .006). Most clients used internal validation of indicators to assess their recovery (79%). Conclusion: Results indicate that clients and caregivers from India perceive recovery as being symptom free, able to go back to work and being independent. Clients with schizophrenia use internal validation to assess recovery. Gender does not play a role in the perceptions toward recovery in schizophrenia. These results will help in developing models of recovery for severe mental illness in Indian context leading to tailored interventions.